Analysis of the transient thermal behaviour of a solar honeycomb (SHC) façade element with and without integrated PV cells. (January 2016) - Brandl, D.; Mach, T.; Hochenauer, C.
Highlights: 3D CFD models were used to simulate the thermal behaviour inside a SHC façade. In an experiment a transient heating phase of a SHC façade element was performed. The influence of the time-step size on the thermal behaviour was analysed. Different SHC materials were used for a comparison during the heating phase. The impact of hourly changing climate on the SHC façade element was simulated. Abstract: The transient thermal behaviour of a ventilated solar honeycomb (SHC) façade element was investigated with the help of numerical simulations. Therefore two three-dimensional CFD models were used to consider a SHC façade element with and without attached PV cells at the exterior glass pane. Beside a natural convective flow model also a radiation model with two wavebands was implemented to enable the differentiation between short-wave solar radiation and long-wave thermal radiation. In a laboratory experiment temperatures in the ventilation cavity and the heat flux at the rear wall of the SHC façade were monitored and compared to simulation results. The experiment using a solar simulation device was carried out for one façade element with PV cells at the exterior glass pane and for one façade element without PV cells. The time-step size for the transient simulations was dramatically reduced after the determination of the maximum time-step size, which finally enabled the analysis of the thermal behaviour over a prolonged period (one day or longer) within reasonable simulation durations. Moreover, the impact of the SHC's material properties on the dynamic thermal behaviour was analysed with the three-dimensional CFD-model. Differences in heating rate, heat flux and temperatures were determined and compared by using five different materials instead of the cellulose honeycomb. Finally this study obtained the impact of hourly changing external climate conditions on the thermal behaviour of a single 1 × 1 m SHC façade element using climate data from a cold winter's day and a hot summer's day which were measured in Graz, Austria.